Optimization of the Development of the Tambak Lorok Floating Solar Power Plant for Self-Consumption (SC) through a Technical and Economic Analysis - Much Bahrun Idris; Heri Susanto; Jaka Windarta (Jurnal IPTEK Bagi Masyarakat, 2026)
Global climate change and rising greenhouse gas (GHG) emissions demand an accelerated transition from fossil fuels to sustainable energy systems. Floating solar power plants (FSPs) are one strategy for integrating renewable and conventional energy sources by utilizing water bodies without causing land-use conflicts. However, this implementation faces challenges related to fluctuations in solar irradiance, aquatic environmental characteristics, and economic uncertainty in investment, particularly for self-consumption schemes at existing power plants such as the Tambak Lorok Combined Cycle Power Plant (CCPP) in Semarang City. This study aims to analyze the technical feasibility, contribution to CO₂ emission reduction, and economic viability of developing a floating PV plant at Tambak Lorok. The research methodology employs a quantitative-analytical approach based on secondary data and system simulation. The study utilizes data on solar irradiance, meteorology, technical specifications of modules and inverters, electricity consumption data from the gas-fired power plant, and project economic parameters. The analysis was conducted through technical, environmental, economic, and integrative approaches. The results show that a 1.166 MWp floating solar power plant system is capable of generating approximately 1,810 MWh of electricity per year, with a performance ratio (PR) of around 85%, indicating efficient system performance. From an environmental perspective, this system has the potential to reduce carbon emissions by approximately 1,085 tons of CO₂ per year, or about 32,558 tons of CO₂ over the project’s 30-year lifespan.Economically, the project is deemed viable, with a net present value (NPV) of Rp5.45 billion, an internal rate of return (IRR) of 12.8%, and a payback period of 11.48 years. These results indicate that the development of a floating solar power plant in Tambak Lorok is technically feasible, provides significant environmental benefits, and is economically profitable, thereby having the potential to serve as a model for the energy transition of fossil-fuel-based power plants in Indonesia.